2020
DOI: 10.2495/arc200121
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical and Mechanical Properties of Compressed Earth Blocks Containing Fibres: By-Product of Okra Plant and Polymer Waste

Abstract: Municipal wastes such as water sachets and agricultural by-products in Burkina Faso need proper management to limit their hazards to the environment. This study investigated the effect of incorporation of fibres from agricultural by-products (okra plant fibre) and water sachet wastes (polymer fibre) on thermophysical and mechanical properties of stabilized compressed earth blocks (CEBs). The CEBs were moulded from moistened mixtures of clayey earthen material stabilized with 10 wt.% CCR (calcium carbide residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It is observed that by increasing the cane bagasse content from 0.5% to 1.0% the absorption of the blocks increases, varying the average value from 14.37 to 14.85% representing an increase of 3.34%. [31] Analyzed okra plant fibers in 0.2, 0.4 and 0.8% by weight of soil in CEB. In the results it was obtained that by increasing the fiber content the absorption increases, obtaining as results 21.2, 22.2 and 22.22% respectively.…”
Section: Results and Analysismentioning
confidence: 99%
“…It is observed that by increasing the cane bagasse content from 0.5% to 1.0% the absorption of the blocks increases, varying the average value from 14.37 to 14.85% representing an increase of 3.34%. [31] Analyzed okra plant fibers in 0.2, 0.4 and 0.8% by weight of soil in CEB. In the results it was obtained that by increasing the fiber content the absorption increases, obtaining as results 21.2, 22.2 and 22.22% respectively.…”
Section: Results and Analysismentioning
confidence: 99%
“…The curing was carried out in ambient conditions, at the production moisture, for 45 days and 28 days respectively for CEBs stabilised with lime or lime:ash [10] and cement [18]. The cured CEBs were dried to constant mass [5], before the treatment by exposure to various conditions.…”
Section: Materials and Methods For The Production Of Cebsmentioning
confidence: 99%
“…In the local context of Burkina Faso, similar studies have specifically focused on the stabilization using industrial binders (cement or lime), geopolymer binders, plant fibers or industrial and agricultural by-products in order to enhance the physical and mechanical performances and durability of CEB for applications in building wall constructions (Ouedraogo et al, 2015;Nshimiyimana et al, 2018;Sore et al, 2018;Nshimiyimana et al, 2020aNshimiyimana et al, , 2020bNshimiyimana et al, , 2020cNshimiyimana et al, , 2020dNshimiyimana et al, forthcoming). Additionally, a number of studies has assessed the potential of CEBs as masonry material for improving the indoor comfort and potentially reduce the energy consumption for air-conditioning (Hema et al, 2017;Moussa et al 2019;Hema et al, 2020;Hema et al, forthcoming).…”
Section: Introductionmentioning
confidence: 99%